Gold Nanorod Assisted Enhanced Plasmonic Detection Scheme of COVID‐19 SARS‐CoV‐2 Spike Protein. Issue 11 (4th October 2020) - Das, Chandreyee Manas; Guo, Yan; Yang, Guang; Kang, Lixing; Xu, Gaixia; Ho, Ho‐Pui; Yong, Ken‐Tye
Abstract: The beautiful interplay between light and matter can give rise to many striking physical phenomena, surface plasmon resonance (SPR) being one of them. Plasmonic immunosensors monitor refractive index changes that occur as a result of specific ligand–analyte or antibody–antigen interactions taking place on the sensor surface. The coronavirus disease (COVID‐19) pandemic has jeopardized the entire world and has resulted in economic slowdown of most countries. In this work, a model of a sandwich plasmonic biosensor that utilizes gold nanorods (Au NRs) for the detection of COVID‐19 SARS‐CoV‐2 spike protein is presented. Simulation results for different prismatic configurations for the basic Kretschmann layout are presented. It is found that a BK7 glass prism‐based SPR sensor has an incremental sensitivity of 111.11 deg RIU −1 . Additionally, using Comsol Multiphysics the electric field enhancement observed for various aspect ratios and layouts of Au NRs are discussed in depth. Abstract : The coronavirus disease (COVID‐19) pandemic has adversely affected the entire world, where apart from stressing the medical fraternity, it has resulted in a major economic slowdown. In this paper, a unique detection scheme for quantifying SARS‐CoV‐2 virus using a plasmonic immunosensor that uses gold nanorods for signal amplification is presented.